Convective Heat Exchange in Downward Moving Liquid under Conditions of Over-Critical Pressures - G. I. Isaev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents some results of experimental investigations on convective heat exchange to laminar n-heptane flow under conditions of over-critical pressure. The case has been considered when directions of forced and free motion are mutually opposite.Under condition tc ≥ tm some specific heat exchange modes being peculiar for the area of over-critical pressure have been determined.On the basis of experimental data on n-heptane heat exchange recommendations for the evaluation of heat exchange intensity as for viscous so for viscous and gravitation modes have been elaborated.